Microglial Cells as a Link between Cannabinoids and the Immune Hypothesis of Psychiatric Disorders - Lisboa, Sabrina F.; Gomes, Felipe V.; Guimaraes, Francisco S.; Campos, Alline C. (Frontiers in Neurology, 2016)
Psychiatric disorders are one of the leading causes of disability worldwide. Although several therapeutic options are available, the exact mechanisms responsible for the genesis of these disorders remain to be fully elucidated. In the last decade, a body of evidence has supported the involvement of the immune system in the pathophysiology of these conditions. Microglial cells play a significant role in maintaining brain homeostasis and surveillance. Dysregulation of microglial functions has been associated with several psychiatric conditions. Cannabinoids regulate the brain-immune axis and inhibit microglial cell activation. Here we summarized evidence supporting the hypothesis that microglial cells could be a target for cannabinoid influence on psychiatric disorders such as anxiety, depression, schizophrenia and stress-related disorders.